2016
DOI: 10.1177/1369433216630461
|View full text |Cite
|
Sign up to set email alerts
|

Study of vertical bending vibration behavior of continuous prestressed concrete box girders with corrugated steel webs

Abstract: Prestressed concrete girders with corrugated steel webs have received considerable attention in the past two decades due to their light self-weight and high prestressing efficiency. Most previous studies were focused on the static behavior of corrugated steel webs and simple beams with corrugated steel webs. The natural frequencies are very important characteristics when evaluating the dynamic responses of a bridge under external loads; however, very few studies have been conducted to investigate the dynamic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In equation. (21), C p1 is much less than 1 for one or more deviators (n ≥ 5 in Tables 2 and 3) along beam span; usually P 0 t ≪ EI(π/l) 2 the critical load of stability, EP effect, or C p1 P 0 t on ω 1 is slight. For high-order frequencies ω i , i ≥ 2, C pi values increase, but the high-order critical loads of stability EI(iπ/l) 2 increase more rapidly, and EP effect on high-order frequency is also slight.…”
Section: Numerical Examplesmentioning
confidence: 95%
See 2 more Smart Citations
“…In equation. (21), C p1 is much less than 1 for one or more deviators (n ≥ 5 in Tables 2 and 3) along beam span; usually P 0 t ≪ EI(π/l) 2 the critical load of stability, EP effect, or C p1 P 0 t on ω 1 is slight. For high-order frequencies ω i , i ≥ 2, C pi values increase, but the high-order critical loads of stability EI(iπ/l) 2 increase more rapidly, and EP effect on high-order frequency is also slight.…”
Section: Numerical Examplesmentioning
confidence: 95%
“…e first-order tendon deformation is caused almost only by the first symmetric mode, very little by other symmetric modes; therefore, the stiffness of tendon E t A t mainly increases the frequency of the first symmetric mode (ω 2 ) and slightly influences the frequency of the other symmetric modes (ω 4 , ω 6 ...) in equation (22). e stiffness of tendon E t A t does not influence the frequencies of the antisymmetric modes (ω 1 , ω 3 ...) in equation (21). Comparing ω 2 values of M① among 8 beams, it shows that as the eccentricity and tendon area increase, ω 2 values increase, but ω 2 values are slightly related to the tendon A or B layout, so the influence of tendon layout linear transformation on the frequency is negligible.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, a great deal of basic research has been conducted on flexural and shear performance of CBGCSW, as well as on buckling of CSW (Chan et al, 2002; He et al, 2014; Ji et al, 2016; Sayed-Ahmed, 2001), while only a little research has been carried out with respect to the torsional performance, especially in nonlinear analysis. Yang et al (2012) and Ma et al (2016) have indicated that Second Theory of A.A Umanskii can well predict the torsional performance of CBGCSW in elastic stage.…”
Section: Introductionmentioning
confidence: 99%